The properties of radio and mid-infrared detected galaxies and the effect of environment on the co-evolution of AGN and star formation at z ∼ 1. Issue 4 (15th April 2020) - Shen, Lu; Lemaux, Brian C; Lubin, Lori M; McKean, John; Miller, Neal A; Pelliccia, Debora; Fassnacht, Christopher D; Tomczak, Adam; Wu, Po-Feng; Kocevski, Dale; Gal, Roy; Hung, Denise; et al.
ABSTRACT: In this study, we investigate 179 radio-infrared (IR) galaxies drawn from a sample of spectroscopically confirmed galaxies, which are detected in radio and mid-IR (MIR) in the redshift range of 0.55 ≤ z ≤ 1.30 in the Observations of Redshift Evolution in Large Scale Environments (ORELSE) survey. We constrain the active galactic nuclei (AGN) contribution to the total IR luminosity ( f AGN ), and estimate the AGN luminosity ( L AGN ) and the star formation rate (SFR). Based on the f AGN  and radio luminosity, radio–IR galaxies are split into galaxies that host either high- or low- f AGN  AGN (high-/low- f AGN ), and star-forming galaxies (SFGs) with little to no AGN activity. We study the properties of the three radio–IR sub-samples comparing to an underlying parent sample. In the comparison of radio luminosity of three sub-samples, no significant difference was found, which could be due to the combined contribution of radio emission from AGN and star formation. We find a positive relationship between L AGN  and specific SFR (sSFR) for both AGN sub-samples, strongly suggesting a co-evolution scenario of AGN and SF in these galaxies. A toy model is designed to demonstrate this co-evolution scenario, where we find that, in almost all cases, a rapid quenching time-scale is required, which we argue is a signature of AGN quenching. The environmental preference for intermediate/infall regions of clusters/groups remains across the co-evolution scenario, which suggests that galaxies might be in an orbital motion around the cluster/group during the scenario.